2015
DOI: 10.1016/j.stemcr.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Adult Hippocampal Neurogenesis and Cognitive Impairments following Prenatal Treatment of the Antiepileptic Drug Valproic Acid

Abstract: SummaryPrenatal exposure to valproic acid (VPA), an established antiepileptic drug, has been reported to impair postnatal cognitive function in children born to VPA-treated epileptic mothers. However, how these defects arise and how they can be overcome remain unknown. Using mice, we found that comparable postnatal cognitive functional impairment is very likely correlated to the untimely enhancement of embryonic neurogenesis, which led to depletion of the neural precursor cell pool and consequently a decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 63 publications
7
77
0
Order By: Relevance
“…Specifically, Juliandi et al (2015) reported that prenatal exposure to VPA increased embryonal cortical neurogenesis but decreased a long-term adult hippocampal neurogenesis [16]. They also reported on aberrant morphological characteristics of DG DCX(+) neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Juliandi et al (2015) reported that prenatal exposure to VPA increased embryonal cortical neurogenesis but decreased a long-term adult hippocampal neurogenesis [16]. They also reported on aberrant morphological characteristics of DG DCX(+) neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that physical activity could partially restore neurogenesis and cognitive deficits caused by the developmental exposure to VPA [16]. …”
Section: Introductionmentioning
confidence: 99%
“…*P b 0.05; **P b 0.01; NS, not significant. hippocampus (Juliandi et al, 2015), so we checked the Wnt signaling and mTOR signaling in these brain tissues of VPA-exposed rat. Our study shows that Wnt signaling and mTOR signaling are activated in the brain tissues of VPA-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our study demonstrated that VPA increased the percentage of β-III-tubulin- or MAP-2-positive neurons. However, a previous study has found that VPA-treated mice (300 mg/kg) have a decreased level of postnatal neurogenesis in the hippocampus, this is presumably due to a slower differentiation of the residual NPCs caused by depletion of the NPC pool [48]. These seemingly contradictory findings could imply that VPA-mediated various effects might depend on the cell type, context of VPA usage, and experimental design used.…”
Section: Discussionmentioning
confidence: 99%